Presentations on progress updates in common bean crop improvement within the Central American Cooperative Program for Crop and Animal Improvement (PCCMCA). - Buendia, Hector Fabio; Aragon, Jorge; Valderrama, Luis; Wilker, Jennifer; Polania, Jose Arnulfo; Espitia Ortiz, Ernesto; Beebe, Stephen; Cadena, Christian (2025)
This research addresses two key challenges for common bean: adaptation to high temperatures and improvement of grain nutritional value, specifically iron content, without negatively affecting crop yield.